Clinical and Radiographic Evaluation of Multilevel Lateral Lumbar Interbody Fusion in Adult Degenerative Scoliosis. Issue 8 (October 2019) - Katz, Austen D.; Singh, Hardeep; Greenwood, Matthew; Cote, Mark; Moss, Isaac L.
Abstract : Study Design: Retrospective review of prospective data. Objective: The objective of this study was to describe the clinical, radiographic, and complication-related outcomes through ≥1-year of 27 patients who underwent lateral lumbar interbody fusion (LLIF) with posterior instrumentation to treat ≥3 contiguous levels of degenerative lumbar scoliosis. Summary of Background Data: Multilevel disease has traditionally been treated with open posterior fusion. Literature on multilevel LLIF is limited. We present our experience with utilizing LLIF to treat multilevel degenerative scoliosis. Methods: Clinical outcomes were evaluated using VAS, SF-12, and ODI. Radiographic outcomes included pelvic tilt, pelvic incidence, lumbar lordosis, pelvic incidence-lumbar lordosis mismatch, Cobb angle, and cage subsidence. Perioperative and long-term complications through the ≥1-year final-postoperative visit were reviewed; transient neurological disturbances were assessed independently. Demographic, comorbidity, operative, and recovery variables, including opioid use, were explored for association with primary outcomes. Results: Mean time to final-postoperative visit was 22.5 months; levels treated with LLIF per patient, 3.7; age, 66 years; and lateral operative time, 203 minutes. EBL was ⩽100 mL in 74% of cases. Clinical outcomes remained significantly improved at ≥1-year. Cobb angle was corrected from 21.1 to 7.9 degrees ( P <0.001), lordosis from 47.3 to 52.6 degrees ( P <0.001), and mismatch from 11.4 to 6.4 degrees ( P =0.003). High-grade subsidence occurred in 3 patients. Subsidence did not significantly impact primary outcomes. In total, 11.1% returned to the operating room for complication-related intervention over nearly 2-years; 37% experienced complications. Experiencing a complication was associated with having an open-posterior portion ( P =0.048), but not with number of LLIF levels treated, or with clinical or radiographic outcomes. No patients experienced protracted neurological deficits; psoas weakness was associated with increased lateral operative time ( P =0.049) and decreased surgeon experience ( P =0.028). Conclusions: Patients who underwent multilevel LLIF with adjunctive posterior surgery had significant clinical and radiographic improvements. Complication rates were similar compared to literature on single-level LLIF. LLIF is a viable treatment for multilevel degenerative scoliosis.